Effects of GLP-1 agonists and SGLT2 inhibitors during pregnancy and lactation on offspring outcomes: a systematic review of the evidence - Muller, Dion R. P.; Stenvers, Dirk J.; Malekzadeh, Arjan; Holleman, Frederik; Painter, Rebecca C.; Siegelaar, Sarah E. (Frontiers in Endocrinology, 2023)
Aims/hypothesis Glucagon-like peptide 1 (GLP-1) agonists and sodium-glucose co-transporter-2 (SGLT2) inhibitors are novel drugs which have recently seen rapid uptake in the treatment of type 2 diabetes and obesity. The paucity of data regarding their safety during pregnancy and lactation causes a dilemma for the physician. The aim of the present study was to systematically review all available data on the offspring effects of GLP-1 agonists and SGLT2 inhibitors during pregnancy and lactation. Methods We systematically searched PubMed, clinicaltrials.gov, FDA and EMA product information on GLP-1 agonists and SGLT2 inhibitors in pregnancy and lactation from inception up to 19 April 2022 without language restrictions. We approached both the Netherlands Pharmacovigilance Centre Lareb on January 17th 2023 and the Teratology Information Service (TIS) of Switzerland on February 6th 2023. Eligible studies investigating the safety (including congenital anomalies, fetal growth, perinatal demise) in animals or humans, or reporting the degree of transfer of these drugs to the fetus, breast milk or breastfed neonate. Two reviewers independently assessed and selected studies for inclusion and subsequently resolved discrepancies by discussion. Results We included 39 records (n=9 theoretical; based on drug properties, n=7 human; n=23 animal, including 76 human offspring, and an unknown number of animal offspring as these numbers could not be retrieved from the FDA and EMA product information). In animal studies, GLP1-agonists were associated with reduced fetal weight and/or growth, delayed ossification and skeletal variants, usually associated with a reduction in maternal weight gain and decreased food consumption. Exendin-4 (GLP1-agonist) was not transported across the maternal-fetal placental interface. In human studies, exenatide (GLP1-agonist) showed a fetal-to-maternal peptide concentration ratio of ≤ 0.017 in ex vivo human placental perfusion in a single placenta. Liraglutide (GLP1-agonist) showed no significant maternal to fetal transfer at least 3.5 hours after maternal exposure in a human study with one subject. In animal studies, GLP-1 agonists were excreted in breast milk; human data on excretion were not available. In animal studies, SGLT2 inhibitors were generally safe during the first trimester but exposure during postnatal day 21 to 90 in juvenile rats, a period coinciding with the late second and third trimester of human renal development, caused dilatation of the renal pelvis and tubules. Human data consisted of a pharmaceutical database of inadvertent pregnancies during SGLT2 inhibitor use, which found an increase in miscarriages and congenital malformations. In animal studies SGLT2 inhibitors were excreted in breast milk and affected neonatal growth, but human data are not available. Conclusion/interpretation We found evidence for adverse offspring effects of GLP-1 agonists and SGLT2 inhibitors also in human studies. Our findings broadly support the advice to discontinue GLP-1 agonists and SGLT2 inhibitors during pregnancy and lactation, and also support the ongoing registration of pregnancy outcomes in pharmacological databases since the amount of available data is scarce and mostly limited to animal studies. Registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=219877